Rise, Fall and Rebirth of Listán Prieto in the Southern Cone of America [la Variedad de Uva País (Listán Prieto) en el Cono Sur de América: Trayectoria Histórica] - Lacoste, P (Universidad de Tarapaca, 2021)
This article studies the historical itinerary of the Uva País variety (Listán Prieto) in Argentina, Chile and Peru. Its process of ascent, hegemony, decline and resurgence is distinguished. At each stage, the cultivated area, uses (especially wines and spirits) and social valuation are examined. It is concluded that, after 150 years of devaluation due to the rise of the French paradigm, the Country Grape has begun a recovery process due to its symbolic dimension and its significance as ancestral heritage. © 2021, Universidad de Tarapaca. All rights reserved.